Influence of NPK fertilization on growth, yield and economics of sunflower (Helianthus annuus L.) varieties and hybrids: INFLUENCE OF NPK FERTILIZATION ON SUNFLOWER - K ASHOK KUMAR,; S NEELIMA,; P MUNIRATHNAM,; A S R SARMA, (Journal of Oilseeds Research, 2013)
A field experiment was conducted at Regional Agricultural Research Station, Nandyal, Andhra Pradesh during 2007 and 2009 to study the comparative assessment of hybrids over varieties grown under rainfed condition with different levels of fertilizers. The resultsrevealed that application of 100 and 150% RDF produced large sized heads (12.8 and 12.9 cm, respectively) coupled with higher seed weight (5.2 g/100 seeds) lead to higher seed yields (921 and 863 kg/ha, respectively). The magnitude of seed yield increase with 100 and 150% RDF was 31.1 and 39.9%, respectively over control. Among the genotypes evaluated,significantly higherseed yield (906 kg/ha) was obtained with NDSH-1 followed bySunbred (866 kg/ha). Application of 150% RDF produced higher netreturns(`10,301/ha) whereas the B:C ratio recorded with 150% RDF was equal to that of 100% RDF.